1969
DOI: 10.1002/cjce.5450470511
|View full text |Cite
|
Sign up to set email alerts
|

Free convection boundary‐layer flow over horizontal plates and discs

Abstract: Free convection flows near horizontal surfaces are discussed for those cases in which a similarity solution can be obtained. Particular cases considered are those of asymptotically large and vanishingly small Prandtl numbers. The solution for the relevant velocity, temperature and pressure functions has to be carried‐out numerically. For the particular cases when the Prandtl number is either sufficiently large, or sufficiently small, this integration would yield general functions, no longer dependent on the Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1969
1969
1994
1994

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…There appears to be no experimental data for predominantly laminar flow in water. The data of Reilly, Tien & Adelman (1966) (used by Rotem & Claassen (19696) in comparisons with their laminar flow analyses) appear to have been obtained in the predominantly turbulent flow regime and agree closely with the experimental correlation for this type of flow obtained by Fishenden & Saunders (1950) in air. Apparently, predominantly turbulent flow is not markedly sensitive to Prandtl number changes, a t least in the range 0.72 < Pr < 10.…”
Section: Lam Inar Natural Convection Boundary Layers On Horizontal Plates 269supporting
confidence: 82%
“…There appears to be no experimental data for predominantly laminar flow in water. The data of Reilly, Tien & Adelman (1966) (used by Rotem & Claassen (19696) in comparisons with their laminar flow analyses) appear to have been obtained in the predominantly turbulent flow regime and agree closely with the experimental correlation for this type of flow obtained by Fishenden & Saunders (1950) in air. Apparently, predominantly turbulent flow is not markedly sensitive to Prandtl number changes, a t least in the range 0.72 < Pr < 10.…”
Section: Lam Inar Natural Convection Boundary Layers On Horizontal Plates 269supporting
confidence: 82%
“…Later Gill, extended Stewartson's solution to another type of wall-temperature variation and to Pr = 1 and 10. Gill et al (1965) and Rotem (1967) showed that the first of the two possible cases of flow was the only one for which boundary-layer solutions could be obtained. At first sight this seems to conflict with early photographs by Schmidt (1932), but this contradiction is only apparent: it can be shown that the flow below a heated plate facing downwards cannot be described by boundary-layer type equations.…”
Section: Introductionmentioning
confidence: 99%
“…Heat is absorbed progressively as the fluid flows over the plate inducing a transverse pressure gradient and it is the variation of this favourable pressure gradient which drives the flow. Apart from a minor error in the sign of the gravity component, pointed out by Gill et al [2], the main features of Stewartson's solution have been supported by the experiments of Rotem and Claassen [3,4] and Pera and Gebhart [5]. Subsequent extensions to Stewartson's work were given by Jones [6], Clarke and Riley [7], Traughot [8] and Ackroyd [9].…”
Section: Introductionmentioning
confidence: 84%